Generation of hybrid grids over plane domains - Kucwaj, Jan (Computer Assisted Methods in Engineering and Science; Vol 7 No 4 (2000), 2023)
The paper presents an algorithm of coverage 2-D multiconnected domain by trianlges and quadrilaterals. The zone covered with quadrilaterals is structured, thus the zone covered with triangles is unstructured. The density of the structured grid is controlled only on one of the surrounding loop, on which the points are generated with mesh density function. Unstructured zone is triangulated by using Delaunay advancing front technique triangulation of points previously generated.